Industrial land price between China's Pearl River Delta and Southeast Asian regions: Competition or Coopetition?. (February 2017) - Zhang, Xiaoling; Lin, Yanliu; Wu, Yuzhe; Skitmore, Martin
Highlights: We model the industrial land price mechanism in the form of a cooperative game. We argue that governments' low land price strategies should be discontinued. We provide policy suggestions for two regions to shift towards a coopetitive model. Abstract: The planned economy system's previous form of industrial land market control in China has led to current market failure because of a large amount of industrial land being sold at a very low price, causing extensive overuse of land and negative effects on land management. As the "World Factory", the Pearl River Delta (PRD) is well known for its rapid urbanization largely driven by Foreign Direct Investment in labor-intensive industries. A low-land price strategy has been commonly adopted by the local government in order to attract industrial investment. In the past decade, the PRD has increasingly faced the increasing competition from its neighboring competition from its neighboring countries in Southeast Asia that have established preference policies to attract FDI and foreign enterprises. Despite a growing body of literature on the internal forces of industrial land in China, little is known of the external forces involved except for the importance of FDI and the intensity of interregional competition between China and other countries in attempting to attract foreign investment. This research fills the knowledge gap by modeling the situation in the form of an international cooperative game model aimed at revealing the industrial land price formation mechanism between the PRD region and Southeast Asian regions. The conditions of industrial land in the area and several Southeast Asian countries are first analyzed for their industrial land price movements in recent years. A game theoretic model is then built that exhibits similar characteristics. The result indicates that the governments' low land price strategy and the competition between the PRD and its neighboring countries have created unnecessarily high social and environmental costs. Policy suggestions are made to encourage a more appropriate use of industrial land in China, and the most important being the need for a mindset shift from competition towards coopetition between the PRD and Southeast Asian regions.